Effects of seed treatments on the germination of Golkoy palm (Phoenix theophrasti Greuter subsp. golkoyana Boydak) - Parlak, Salih (My University, 2023)
Datça palm (Phoenix theophrasti Greuter) is the only palm taxa in the European continent. Its subspecies, Golkoy palm (Phoenix theophrasti Greuter subsp. golkoyana Boydak) was recorded only in Turkey. This subspecies, which spreads in sensitive ecosystems, needs to be carefully protected. Although there are three natural populations of Datça palm in Turkey, there is only one population of Gölköy palm. This population is under threat due to factors such as tourism, pollution, urbanization, use of groundwater and forest fires. In this respect, the continuity of the species should be ensured by taking in-situ and ex-situ protection measures immediately. One of the ex-situ conservation measures involves the propagation of the species from seed. Cold-wet stratification is applied to remove dormancy in Gölköy palm seeds. In this study, GA3, ultrasound and vacuum applications at different times were applied to remove dormancy in seeds and shorten germination time. At the end of the study that lasted for 10 weeks, it was determined that GA3, vacuum and ultrasonic applications increased the germination rate of the seeds and shortened the germination period. While the highest germination rate was reached in the seeds treated with GA3, (91.4%), the germination rate was 88.3% and 88.6%, respectively, in 60 and 120 min ultrasound applications. The germination rate of the seeds in which vacuum was applied for 60 and 120 minutes was found to be 29.9% and 48%, respectively. The lowest germination was 6.3% in the control group seeds.
Keywords: GA3; seed germination; Golkoy palm; ultrasound and vacuum treatments